Ozone therapy in a patient with epicondylitis and bone oedema - Antonino Genovese, Graziella Tindera Giuffrè, Dario Iannelli, Filippo Iannelli (Pathos)
Epicondylitis is a debilitating condition of the elbow. The pain in the upper extremity is usually sharp and excruciating, limiting mobility and affecting work activity and quality of life. The patient usually reports unilateral attacks of pain that begin abruptly and last for varying lengths of time. The authors present a clinical case of a 48-year-old patient suffering from epicondylitis and bone oedema secondary to sports overuse. This study shows that treatment with Ozone therapy proved effective in both pain control and reduction of bone oedema.